2005
DOI: 10.1021/bi0504254
|View full text |Cite
|
Sign up to set email alerts
|

G Protein βγ Dimer Formation:  Gβ and Gγ Differentially Determine Efficiency of in Vitro Dimer Formation

Abstract: The Gbeta and Ggamma subunit of the heterotrimeric G proteins form a functional dimer that is stable once assembled in vivo or in vitro. The requirements, mechanism, and specificity of dimer formation are still incompletely understood, but represent important biochemical processes involved in the specificity of cellular signaling through G proteins. Here, seven Gbeta and 12 FLAG-epitope-tagged Ggamma subunits were separately synthesized in vitro using a rabbit reticulocyte lysate expression system. The transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
75
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(84 citation statements)
references
References 53 publications
9
75
0
Order By: Relevance
“…With the exception of the β 5 -subunit, all combinations of the other four β-subunits (β 1 -β 4 ) and 12 γ-subunits (γ 1 -γ 5 and γ 7 -γ 13 ) were found to interact with the two different α-subunits. This finding was unexpected because other investigators had indicated that certain βγ-dimers (e.g., β 2 γ 1 , β 2 γ 11 , β 2 γ 13 , β 3 γ 1 , and β 3 γ 11 ) do not exist (6,(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…With the exception of the β 5 -subunit, all combinations of the other four β-subunits (β 1 -β 4 ) and 12 γ-subunits (γ 1 -γ 5 and γ 7 -γ 13 ) were found to interact with the two different α-subunits. This finding was unexpected because other investigators had indicated that certain βγ-dimers (e.g., β 2 γ 1 , β 2 γ 11 , β 2 γ 13 , β 3 γ 1 , and β 3 γ 11 ) do not exist (6,(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 93%
“…Previous βγ-dimerization studies have used various expression systems [e.g., in vitro translation (32,33), Sf9 cells (26), yeast (29), and mammalian cells (27,28,30,31,34)] and various dimerization assays [e.g., coimmunoprecipitation (30)(31)(32), yeast two-hybrid screens (29), membrane targeting of the β-subunit (27), purification of functional dimers (26,28), and bimolecular fluorescence complementation (a complementation of YFP from two fragments) (34)]. An important difference from other studies is our mode of expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations